Evaluation of routine contrast swallow following total pharyngolaryngectomy and free jejunal transfer. (17th April 2015) - Fujiki, Masahide; Miyamoto, Shimpei; Hayashi, Ryuichi; Sakuraba, Minoru
<x xml:space="preserve">Abstract</x> Objective Anastomotic leakage is a serious complication following total pharyngolaryngectomy (TPL) and free jejunal transfer (FJT). Although routine radiological assessment using contrast swallow is widely performed postoperatively for the detection of anastomotic leakage before oral intake, the accuracy remains unclear. We evaluated the clinical usefulness of routine contrast swallow for screening of anastomotic leakage. Study Design Retrospective chart review. Methods We retrospectively reviewed 232 patients who had undergone TPL and FJT from 2009 to 2013. Initial contrast swallow was performed near the seventh postoperative day in patients without a history of radiation for head and neck region preoperatively and near the 14th postoperative day in patients with a history. The accuracy of routine contrast swallow was calculated. Results Clinical anastomotic leakage occurred in 12 patients (5.2%); of these, anastomotic leakage was detected by initial contrast swallow in six patients. The sensitivity and specificity of contrast swallow were 50.0% and 99.1%, respectively. Conclusion Contrast swallow has low sensitivity and a high false‐negative rate for the diagnosis of clinical leakage after TPL and FJT, and routine contrast swallow was insufficient for the screening of anastomotic leakage. Therefore, contrast swallow should be performed in a targeted fashion for patients with clinical signs of anastomotic leakage. Level of Evidence 4. Laryngoscope, 125:2280–2283, 2015